Solid electrolyte and electricity storage device
By adding a specific proportion of lithium, phosphorus, sulfur, halogen and aluminum elements to the solid electrolyte to form a crystal structure with high ion conductivity, the problem of low ion conductivity of solid electrolytes in the prior art is solved, and higher charge and discharge performance and energy density are achieved.
Patent Information
- Application Number
- CN202380062787.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-27
- Filing Date
- 2023-08-24
- Publication Date
- 2025-04-18
AI Technical Summary
In the prior art, the ion conductivity of solid electrolytes is low, making it difficult to meet the needs of high energy density and fast charging and discharge.
A solid electrolyte containing lithium, phosphorus, sulfur, halogen and aluminum is used to form a crystal structure with high ion conductivity by adjusting the molar ratio of these elements.
It significantly improves the ion conductivity of solid electrolytes, improves the charge and discharge performance and energy density of the power storage components.
Smart Images

Figure CN119856234A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte and an electricity storage element. Background Art
[0002] Non-aqueous electrolyte secondary batteries, represented by lithium-ion secondary batteries, are widely used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. Non-aqueous electrolyte secondary batteries are generally composed of an electrode body, a non-aqueous electrolyte, and a container. The electrode body has a pair of electrodes and a separator. The container accommodates these electrode bodies and non-aqueous electrolytes, and charges and discharges by transferring charge ions between the two electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium-ion capacitors and double-layer capacitors have also been widely used.
[0003] In recent years, a storage element using a solid electrolyte such as a sulfide solid electrolyte as a non-aqueous electrolyte instead of a non-aqueous electrolyte solution formed by dissolving an electrolyte salt in a liquid such as an organic solvent has been proposed. Patent Document 1 describes a sulfide solid electrolyte containing lithium, phosphorus, and sulfur and having a crystal structure.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-228570 Summary of the invention
[0007] In solid electrolytes, high ion conductivity is important in order to increase the output of power storage devices, etc. Even sulfide solid electrolytes containing lithium, phosphorus, and sulfur as described in Patent Document 1 require materials with high ion conductivity.
[0008] An object of the present invention is to provide a solid electrolyte having high ion conductivity and a power storage device using the solid electrolyte.
[0009] A solid electrolyte according to one aspect of the present invention contains lithium, phosphorus, sulfur, halogen and aluminum, has a crystal structure and satisfies both of the following formulae (a1) and (b1) or both of the following formulae (a2) and (b2).
[0010] 2.89<[Li / P]-[X / P]≤3.15···(a1)
[0011] 0.01≤[Al / P]≤0.10···(b1)
[0012] 2.84<[Li / P]-[X / P]≤2.89···(a2)
[0013] 0.02≤[Al / P]≤0.10···(b2)
[0014] In the above formulas (a1), (b1), (a2) and (b2), [Li / P] is the molar ratio of the lithium element content to the phosphorus element content, [X / P] is the molar ratio of the halogen element content to the phosphorus element content, and [Al / P] is the molar ratio of the aluminum element content to the phosphorus element content.
[0015] Another aspect of the present invention provides an electric storage device including the solid electrolyte.
[0016] According to any aspect of the present invention, a solid electrolyte having high ion conductivity and a power storage device using the solid electrolyte can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic cross-sectional view of an all-solid-state battery which is one embodiment of the electric storage element of the present invention.
[0018] Figure 2 This is a schematic diagram of a power storage device formed by combining a plurality of power storage elements according to one embodiment of the present invention.
[0019] Figure 3 It is a scatter diagram showing the relationship between the values of [Li / P]-[X / P] and [Al / P] and the ion conductivity of Examples 1 to 9 and Comparative Examples 1 to 6. DETAILED DESCRIPTION
[0020] First, the solid electrolyte and the energy storage device disclosed in this specification are briefly described.
[0021] [1] One aspect of the present invention relates to a solid electrolyte containing lithium, phosphorus, sulfur, a halogen and aluminum, and having a crystal structure that satisfies both of the following formulas (a1) and (b1) or both of the following formulas (a2) and (b2).
[0022] 2.89<[Li / P]-[X / P]≤3.15···(a1)
[0023] 0.01≤[Al / P]≤0.10···(b1)
[0024] 2.84<[Li / P]-[X / P]≤2.89···(a2)
[0025] 0.02≤[Al / P]≤0.10···(b2)
[0026] In the above formulas (a1), (b1), (a2) and (b2), [Li / P] is the molar ratio of the lithium element content to the phosphorus element content, [X / P] is the molar ratio of the halogen element content to the phosphorus element content, and [Al / P] is the molar ratio of the aluminum element content to the phosphorus element content.
[0027] The solid electrolyte described in [1] above has high ion conductivity. The reason is not yet clear, but it is presumed to be the following. Halogen elements are considered to be elements that contribute to the formation of a crystal structure with high ion conductivity in a solid electrolyte containing lithium, phosphorus and sulfur. [Li / P]-[X / P] in formulas (a1) and (a2) is an indicator of the content of lithium elements that are not combined with halogen elements. It can be considered that by containing a specified amount of lithium elements that are not combined with halogen elements, the ease of forming a crystal structure with high ion conductivity is maintained, and the content of lithium elements that are easy to contribute to ion conduction can be appropriately increased. It can be considered that for such a crystal structure with high ion conductivity, by containing a specified amount of aluminum elements, the ion conductivity will be further improved due to the change in the crystal structure. In particular, when the content of lithium elements that are not combined with halogen elements is small as shown in formula (a2), by increasing the content of aluminum elements as shown in formula (b2), sufficient crystal structure changes will occur and the ion conductivity will be sufficiently improved. Based on such reasons, it can be inferred that the ion conductivity of the solid electrolyte described in [1] above, which further contains a halogen element and an aluminum element and satisfies both formulas (a1) and (b1) or both formulas (a2) and (b2), is improved compared to the previous solid electrolyte containing lithium, phosphorus and sulfur and having a crystal structure.
[0028] It should be noted that when a sulfide solid electrolyte containing no phosphorus such as Li2S contains boron, the ion conductivity may be improved due to lithium defects caused by the boron. However, solid electrolytes containing lithium, phosphorus and sulfur already have many lithium defects compared to Li2S due to the phosphorus. Therefore, it is believed that the ion conductivity improvement effect caused by lithium defects caused by the boron cannot be fully reflected in solid electrolytes containing lithium, phosphorus and sulfur.
[0029] The solid electrolyte "has a crystal structure" can be confirmed by powder X-ray diffraction measurement. That is, "having a crystal structure" means that a peak from the crystal structure of the solid electrolyte is observed in the X-ray diffraction pattern obtained by the powder X-ray diffraction measurement. The solid electrolyte may also contain an amorphous part. The powder X-ray diffraction measurement is carried out by the following steps. The solid electrolyte powder for measurement is filled into an airtight X-ray diffraction measurement sample holder in an argon atmosphere with a dew point below -50°C. The powder X-ray diffraction measurement is carried out using an X-ray diffraction device (Rigaku's "MiniFlex II"). The ray source is CuKα rays, the tube voltage is 30kV, the tube current is 15mA, the diffracted X-rays pass through a Kβ filter with a thickness of 30μm, and are detected with a high-speed one-dimensional detector (model: D / teX Ultra 2). The sampling width is 0.01°, the scanning speed is 5° / min, the diffusion slit width is 0.625°, the light receiving slit width is 13mm (OPEN), and the scattering slit width is 8mm. In the present invention, "X-ray diffraction pattern using CuKα rays" refers to an X-ray diffraction pattern obtained by the above-mentioned powder X-ray diffraction measurement.
[0030] [2] The solid electrolyte described in [1] above may not contain a boron element, or may further contain a boron element in which the content of the boron element on a molar basis is less than the content of the aluminum element on a molar basis.
[0031] The solid electrolyte described in [2] above has a higher ion conductivity. As described above, even if the solid electrolyte contains boron, the effect of improving the ion conductivity is not fully demonstrated compared to the solid electrolyte containing lithium, phosphorus and sulfur. Therefore, it is speculated that in the solid electrolyte described in [2] above, since the solid electrolyte does not contain boron or the content of boron is small, the essential elements can effectively play a role and suppress the excessive generation of lithium defects, thereby further improving the ion conductivity.
[0032] [3] The solid electrolyte described in [1] or [2] may further contain nitrogen.
[0033] The solid electrolyte described in [3] above has a tendency to have higher ion conductivity. The reason for this is not yet determined, but it is presumed that when nitrogen is contained, a path that is advantageous for lithium ion conduction is formed in the crystal structure.
[0034] [4] In the solid electrolyte described in [3] above, both of the following formulas (a3) and (b3) may be satisfied.
[0035] 2.92≤[Li / P]-[X / P]≤3.07···(a3)
[0036] 0.01≤[Al / P]≤0.07···(b3)
[0037] The solid electrolyte described in [4] above has higher ion conductivity.
[0038] [5] The solid electrolyte described in any one of [1] to [4] above may also be represented by the following formula (1).
[0039] Li a Al b Zn c PS d N e X f Y g ···(1)
[0040] In the above formula (1), X is a halogen element, and Y is an element other than lithium, aluminum, zinc, phosphorus, sulfur, nitrogen and halogen. a, b, c, d, e, f and g are numerical values for giving a stoichiometric ratio, a is a numerical value satisfying 3.00≤a≤4.00, b is a numerical value satisfying 0.01≤b≤0.10, c is a numerical value satisfying 0.00≤c<0.10, d is a numerical value satisfying 3.50≤d≤4.50, e is a numerical value satisfying 0.00≤e≤0.30, f is a numerical value satisfying 0.10≤f≤1.00, and g is a numerical value of 0.00≤g≤0.04.
[0041] The solid electrolyte described in [5] above has higher ion conductivity.
[0042] [6] In the solid electrolyte described in any one of [1] to [5] above, both of the following formulas (a4) and (b4) may be satisfied.
[0043] 2.94≤[Li / P]-[X / P]≤3.05···(a4)
[0044] 0.01≤[Al / P]≤0.06···(b4)
[0045] The solid electrolyte described in [6] above has higher ion conductivity.
[0046] [7] In the solid electrolyte described in any one of [1] to [6] above, the solid electrolyte may also satisfy both of the following formulas (a5) and (b5), both of the following formulas (a6) and (b6), or both of the following formulas (a7) and (b7).
[0047] 3.05<[Li / P]-[X / P]≤3.15···(a5)
[0048] 0.03≤[Al / P]≤0.08···(b5)
[0049] 2.91<[Li / P]-[X / P]≤3.05···(a6)
[0050] 0.01≤[Al / P]≤0.10···(b6)
[0051] 2.84<[Li / P]-[X / P]≤2.91···(a7)
[0052] 0.03≤[Al / P]≤0.08···(b7)
[0053] The solid electrolyte described in [7] above has higher ion conductivity.
[0054] [8] In the solid electrolyte described in any one of [1] to [7] above, the solid electrolyte may also satisfy both of the following formulas (a8) and (b8), both of the following formulas (a9) and (b9), or both of the following formulas (a10) and (b10).
[0055] 3.00<[Li / P]-[X / P]≤3.15···(a8)
[0056] 0.04≤[Al / P]≤0.07···(b8)
[0057] 2.93<[Li / P]-[X / P]≤3.00···(a9)
[0058] 0.01≤[Al / P]≤0.09···(b9)
[0059] 2.84<[Li / P]-[X / P]≤2.93···(a10)
[0060] 0.04≤[Al / P]≤0.07···(b10)
[0061] The solid electrolyte described in [8] above has higher ion conductivity.
[0062] [9] In the solid electrolyte described in any one of [1] to [8] above, both of the following formulas (a11) and (b11) may be satisfied.
[0063] 2.87<[Li / P]-[X / P]≤3.06···(a11)
[0064] 0.03≤[Al / P]≤0.08···(b11)
[0065] The solid electrolyte described in [9] above has higher ion conductivity.
[0066]
[10] In the solid electrolyte described in any one of [1] to [9] above, all of the following formulas (b12), (c12) and (d12) may also be satisfied.
[0067] 0.01≤[Al / P]≤0.03···(b12)
[0068] [Li / P]-[X / P]≤5.00×[Al / P]+2.91···(c12)
[0069] [Li / P]-[X / P]≥-3.50×[Al / P]+2.98···(d12)
[0070] The solid electrolyte described in
[10] above has higher ion conductivity.
[0071]
[11] In the solid electrolyte described in any one of [1] to
[10] above, all of the following formulas (b13), (c13) and (d13) may be satisfied.
[0072] 0.03≤[Al / P]≤0.08···(b13)
[0073] [Li / P]-[X / P]≤3.50×[Al / P]+2.96···(c13)
[0074] [Li / P]-[X / P]≤-2.33×[Al / P]+3.25···(d13)
[0075] The solid electrolyte described in
[11] above has higher ion conductivity.
[0076]
[12] In the solid electrolyte described in any one of [1] to
[11] above, both of the following formulas (a14) and (b14) may be satisfied.
[0077] 2.97≤[Li / P]-[X / P]≤3.06···(a14)
[0078] 0.01≤[Al / P]≤0.05···(b14)
[0079] The solid electrolyte described in
[12] has a higher ion conductivity. In addition, for the solid electrolyte described in
[12] , when the lowest crystallization temperature among a plurality of crystallization temperatures existing in the range of 150°C to 400°C is set to T1 [°C], the crystallization temperature T1 is lowered. As a result, the productivity of the solid electrolyte described in
[12] is improved.
[0080]
[13] In the solid electrolyte described in any one of [1] to
[12] above, all of the following formulas (a15), (b15) and (c15) may be satisfied.
[0081] 2.97≤[Li / P]-[X / P]≤3.06···(a15)
[0082] 0.01≤[Al / P]≤0.03···(b15)
[0083] [Li / P]-[X / P]≤5.00×[Al / P]+2.91···(c15)
[0084] The solid electrolyte described in
[13] above has higher ion conductivity.
[0085]
[14] In the solid electrolyte described in any one of [1] to
[13] above, both of the following formulas (a16) and (b16) may be satisfied.
[0086] 2.97≤[Li / P]-[X / P]≤3.06···(a16)
[0087] 0.03≤[Al / P]≤0.05···(b16)
[0088] The solid electrolyte described in
[14] above has higher ion conductivity.
[0089]
[15] In the solid electrolyte described in any one of [1] to
[14] above, both bromine and iodine are contained as halogen elements, and the molar ratio of the bromine content to the phosphorus content [Br / P] can be 0.05 to 0.50.
[0090] The solid electrolyte described in
[15] above has higher ion conductivity.
[0091]
[16] In the solid electrolyte described in any one of [1] to
[15] above, both bromine and iodine are contained as halogen elements, and the molar ratio [I / P] of the iodine content to the phosphorus content can be 0.05 to 0.50.
[0092] The solid electrolyte described in
[16] above has higher ion conductivity.
[0093]
[17] In the solid electrolyte described in any one of [1] to
[16] above, the molar ratio [S / P] of the sulfur content to the phosphorus content may be 3.50 to 4.50.
[0094] The solid electrolyte described in
[17] above has higher ion conductivity.
[0095]
[18] In the solid electrolyte described in any one of [1] to
[17] above, the molar ratio [N / P] of the nitrogen content to the phosphorus content may be 0.01 to 0.25.
[0096] The solid electrolyte described in
[18] above has higher ion conductivity.
[0097]
[19] The solid electrolyte described in any one of [1] to
[18] above further contains zinc element, and the molar ratio of the zinc element content to the phosphorus element content [Zn / P] can be 0.001 to 0.05.
[0098] The solid electrolyte described in
[19] above has higher ion conductivity.
[0099]
[20] In the solid electrolyte described in any one of [1] to
[19] above, both of the following formulas (a17) and (b17) may be satisfied.
[0100] 2.97≤[Li / P]-[X / P]≤3.06···(a17)
[0101] 0.05≤[Al / P]≤0.08···(b17)
[0102] For the solid electrolyte described in
[20] above, when the lowest crystallization temperature among the plurality of crystallization temperatures existing in the range of 150°C to 400°C is set to T1 [°C] and the highest crystallization temperature among the plurality of crystallization temperatures is set to T2 [°C], the difference T2-T1 between the crystallization temperature T1 and the crystallization temperature T2 becomes larger. As a result, the productivity of the solid electrolyte described in
[20] above is improved.
[0103]
[21] In the solid electrolyte described in any one of [1] to
[20] above, all of the following formulas (b18), (c18) and (d18) may be satisfied.
[0104] 0.01≤[Al / P]≤0.05···(b18)
[0105] [Li / P]-[X / P]≥-4.00×[Al / P]+3.01···(c18)
[0106] [Li / P]-[X / P]≥4.00×[Al / P]+2.77···(d18)
[0107] In the solid electrolyte described in
[21] , when the lowest crystallization temperature among a plurality of crystallization temperatures existing in the range of 150° C. to 400° C. is set to T1 [° C.], the crystallization temperature T1 is lowered. Thus, the productivity of the solid electrolyte described in
[21] is improved.
[0108]
[22] The solid electrolyte described in any one of [1] to
[21] above may also satisfy both of the following formulas (a19) and (b19).
[0109] 2.97≤[Li / P]-[X / P]≤3.15···(a19)
[0110] 0.01≤[Al / P]≤0.08···(b19)
[0111] For the solid electrolyte described in
[22] above, when the lowest crystallization temperature among a plurality of crystallization temperatures existing in the range of 150° C. to 400° C. is set to T1 [° C.], the crystallization temperature T1 is lowered. Thus, the productivity of the solid electrolyte described in
[22] above is improved.
[0112]
[23] Another aspect of the present invention provides an electric storage device including the solid electrolyte according to any one of [1] to
[22] .
[0113] The energy storage device described in
[23] above includes a solid electrolyte having high ion conductivity. Therefore, the energy storage device described in
[23] above has good charge and discharge performance.
[0114] A solid electrolyte, a method for manufacturing a solid electrolyte, a storage element, a method for manufacturing a storage element, a storage device, and other embodiments of an embodiment of the present invention are described in detail. It should be noted that the names of the components (constituent elements) used in each embodiment are sometimes different from the names of the components (constituent elements) used in the background art.
[0115] <Solid electrolyte>
[0116] (Crystal Structure)
[0117] The solid electrolyte involved in one embodiment of the present invention has a crystal structure. The crystal structure of the solid electrolyte is not particularly limited, and preferably includes at least one of the following crystal structures: a crystal structure having diffraction peaks at 2θ of 19.9°±0.5° and 29.3°±0.5° in an X-ray diffraction pattern using CuKα rays (High Ion Conduction Phase: HICP); and a crystal structure having diffraction peaks at diffraction angles 2θ of 21.0±0.5° and 28.0±0.5° in the above X-ray diffraction pattern (Low Ion Conduction Phase: LICP); more preferably including HICP. The ion conductivity of HICP and LICP is high, and the ion conductivity of HICP is higher. Therefore, when the solid electrolyte has such a crystal structure, the ion conductivity is further improved.
[0118] The solid electrolyte may have a crystal structure other than HICP and LICP. Examples of the crystal structure other than HICP and LICP include β-Li3PS4, LGPS type, argyrodite type, Li7P3S 11 , Thio-LISICON series, etc. The solid electrolyte may also have an amorphous portion.
[0119] In the solid electrolyte, there are multiple crystallization temperatures in the range of 150°C to 400°C. When the lowest crystallization temperature among the multiple crystallization temperatures is set to T1[°C] and the highest crystallization temperature among the multiple crystallization temperatures is set to T2[°C], the difference T2-T1 between the crystallization temperature T1 and the crystallization temperature T2 is preferably 50°C or more. If heat treatment is performed when manufacturing the solid electrolyte, HICP may precipitate. It can be considered that if the heat treatment temperature is increased, HICP phase changes to LICP, and if the heat treatment temperature is further increased, the phase changes to β-Li3PS4, etc. The above-mentioned crystallization temperature T1 refers to the precipitation temperature of HICP or LICP. When the solid electrolyte is heat treated according to the composition, LICP is sometimes precipitated without precipitation of HICP. Therefore, the above-mentioned crystallization temperature T1 refers to the precipitation temperature of HICP when HICP precipitates, and refers to the precipitation temperature of LICP when HICP does not precipitate. In addition, the crystallization temperature T2 refers to the precipitation temperature or phase transition temperature of a crystalline phase with low ionic conductivity other than β-Li3PS4 or β-Li3PS4. Therefore, in order to further improve the ionic conductivity of the solid electrolyte, the heat treatment temperature needs to be controlled within a temperature range where HICP or LICP is precipitated and β-Li3PS4 and the like are difficult to generate. Therefore, by making the difference T2-T1 between the crystallization temperature T1 and the crystallization temperature T2 greater than 50°C, the temperature range in which the thermal stability of HICP or LICP is high can be widened. When the temperature range in which the thermal stability of HICP and the like is high is wide, productivity is improved. The lower limit of the difference T2-T1 between the crystallization temperature T1 and the crystallization temperature T2 is more preferably 60°C, more preferably 70°C, more preferably 80°C, and more preferably 100°C. As the upper limit of the difference T2-T1 between the crystallization temperature T1 and the crystallization temperature T2, for example, it can be 160°C, 150°C, 140°C or 135°C. The difference T2-T1 between the crystallization temperature T1 and the crystallization temperature T2 may be, for example, 60°C to 160°C, 70°C to 150°C, 80°C to 140°C, or 100°C to 135°C.
[0120] The upper limit of the crystallization temperature T1 is preferably 195° C., more preferably 190° C. The lower limit of the crystallization temperature T1 may be, for example, 170° C. or 180° C. The crystallization temperature T1 may be, for example, 170° C. to 195° C. or 180° C. to 190° C. When the solid electrolyte has such a crystallization temperature T1, HICP or LICP is precipitated at a low heat treatment temperature, and productivity is improved.
[0121] The "crystallization temperature" of the solid electrolyte is determined by measuring it using a differential scanning calorimeter (DSC) in the following steps. In an argon atmosphere with a dew point below -50°C, the sample powder to be measured (the solid electrolyte before heat treatment of the composition prepared in the method for manufacturing the solid electrolyte) is placed in a stainless steel sealed pan and then sealed with a special clamp. Differential scanning calorimetry is performed using a DSC device (Rigaku's "Thermo Plus DSC8230"). The temperature range is from room temperature to 400°C, and the heating rate is 10°C / min.
[0122] (composition)
[0123] The solid electrolyte contains lithium, phosphorus, sulfur, halogen and aluminum.
[0124] As the halogen element, there can be mentioned fluorine, chlorine, bromine, iodine, etc., preferably bromine and iodine. One or more halogen elements can be used. As the halogen element, it is preferred to contain both bromine and iodine.
[0125] Regarding the constituent elements of the solid electrolyte, when the difference [Li / P]-[X / P] between the molar ratio of the content of the lithium element to the content of the phosphorus element [Li / P] and the molar ratio of the content of the halogen element to the content of the phosphorus element [X / P] is greater than 2.89 and less than 3.15, the molar ratio of the content of the aluminum element to the content of the phosphorus element [Al / P] is 0.01 to 0.10. That is, when the following formula (a1) is satisfied, the following formula (b1) is satisfied.
[0126] 2.89<[Li / P]-[X / P]≤3.15···(a1)
[0127] 0.01≤[Al / P]≤0.10···(b1)
[0128] When [Li / P]-[X / P] is greater than 2.89 and less than 3.15, the molar ratio [Al / P] is preferably 0.01 to 0.08, more preferably 0.01 to 0.07, and sometimes more preferably 0.02 to 0.06. When [Li / P]-[X / P] is greater than 2.89 and less than 3.15, by making the molar ratio [Al / P] within the above range, the crystal structure is appropriately changed due to the aluminum element, and the ion conductivity is improved.
[0129] When [Li / P]-[X / P] is greater than 2.84 and less than 2.89, the molar ratio of the aluminum content to the phosphorus content [Al / P] is 0.02 to 0.10. That is, when the following formula (a2) is satisfied, the following formula (b2) is satisfied.
[0130] 2.84<[Li / P]-[X / P]≤2.89···(a2)
[0131] 0.02≤[Al / P]≤0.10···(b2)
[0132] When [Li / P]-[X / P] is greater than 2.84 and less than 2.89, the molar ratio [Al / P] is preferably 0.03 to 0.08, more preferably 0.04 to 0.07, and further preferably 0.05 to 0.06. When [Li / P]-[X / P] is greater than 2.84 and less than 2.89, by making the molar ratio [Al / P] within the above range, the crystal structure is appropriately changed due to the aluminum element, and the ion conductivity is improved.
[0133] The relationship between [Li / P]-[X / P] and [Al / P] preferably satisfies both of the following formulas (a3) and (b3).
[0134] 2.92≤[Li / P]-[X / P]≤3.07···(a3)
[0135] 0.01≤[Al / P]≤0.07···(b3)
[0136] The relationship between [Li / P]-[X / P] and [Al / P] more preferably satisfies both of the following formulas (a4) and (b4).
[0137] 2.94≤[Li / P]-[X / P]≤3.05···(a4)
[0138] 0.01≤[Al / P]≤0.06···(b4)
[0139] When both the formulas (a3) and (b3) are satisfied, and further when both the formulas (a4) and (b4) are satisfied, the ion conductivity of the solid electrolyte is further improved.
[0140] The relationship between [Li / P]-[X / P] and [Al / P] also preferably satisfies both of the following formulae (a5) and (b5), both of the formulae (a6) and (b6), or both of the formulae (a7) and (b7).
[0141] 3.05<[Li / P]-[X / P]≤3.15···(a5)
[0142] 0.03≤[Al / P]≤0.08···(b5)
[0143] 2.91<[Li / P]-[X / P]≤3.05···(a6)
[0144] 0.01≤[Al / P]≤0.10···(b6)
[0145] 2.84<[Li / P]-[X / P]≤2.91···(a7)
[0146] 0.03≤[Al / P]≤0.08···(b7)
[0147] The relationship between [Li / P]-[X / P] and [Al / P] more preferably satisfies both of the following formulas (a8) and (b8), both of the formulas (a9) and (b9), or both of the formulas (a10) and (b10).
[0148] 3.00<[Li / P]-[X / P]≤3.15···(a8)
[0149] 0.04≤[Al / P]≤0.07···(b8)
[0150] 2.93<[Li / P]-[X / P]≤3.00···(a9)
[0151] 0.01≤[Al / P]≤0.09···(b9)
[0152] 2.84<[Li / P]-[X / P]≤2.93···(a10)
[0153] 0.04≤[Al / P]≤0.07···(b10)
[0154] When both equations (a5) and (b5), both equations (a6) and (b6), or both equations (a7) and (b7) are satisfied, and further when both equations (a8) and (b8), both equations (a9) and (b9), or both equations (a10) and (b10) are satisfied, the ion conductivity of the solid electrolyte is further improved.
[0155] The relationship between [Li / P]-[X / P] and [Al / P] preferably satisfies both of the following formulas (a11) and (b11).
[0156] 2.87<[Li / P]-[X / P]≤3.06···(a11)
[0157] 0.03≤[Al / P]≤0.08···(b11)
[0158] The relationship between [Li / P]-[X / P] and [Al / P] also preferably satisfies all of the following formulae (b12), (c12) and (d12).
[0159] 0.01≤[Al / P]≤0.03···(b12)
[0160] [Li / P]-[X / P]≤5.00×[Al / P]+2.91···(c12)
[0161] [Li / P]-[X / P]≥-3.50×[Al / P]+2.98···(d12)
[0162] The relationship between [Li / P]-[X / P] and [Al / P] also preferably satisfies all of the following formulae (b13), (c13) and (d13).
[0163] 0.03≤[Al / P]≤0.08···(b13)
[0164] [Li / P]-[X / P]≤3.50×[Al / P]+2.96···(c13)
[0165] [Li / P]-[X / P]≤-2.33×[Al / P]+3.25···(d13)
[0166] When both equations (a11) and (b11) are satisfied, when all of equations (c12), (d12) and (b12) are satisfied, and further when all of equations (c13), (d13) and (b13) are satisfied, the ion conductivity of the solid electrolyte is further improved.
[0167] The relationship between [Li / P]-[X / P] and [Al / P] preferably satisfies both of the following formulas (a14) and (b14).
[0168] 2.97≤[Li / P]-[X / P]≤3.06···(a14)
[0169] 0.01≤[Al / P]≤0.05···(b14)
[0170] The relationship between [Li / P]-[X / P] and [Al / P] also preferably satisfies all of the following formulae (a15), (b15) and (c15).
[0171] 2.97≤[Li / P]-[X / P]≤3.06···(a15)
[0172] 0.01≤[Al / P]≤0.03···(b15)
[0173] [Li / P]-[X / P]≤5.00×[Al / P]+2.91···(c15)
[0174] The relationship between [Li / P]-[X / P] and [Al / P] preferably satisfies both of the following formulas (a16) and (b16).
[0175] 2.97≤[Li / P]-[X / P]≤3.06···(a16)
[0176] 0.03≤[Al / P]≤0.05···(b16)
[0177] When both equations (a14) and (b14) are satisfied, when all of equations (a15), (b15) and (c15) are satisfied, and further when both equations (a16) and (b16) are satisfied, the ion conductivity of the solid electrolyte is further improved.
[0178] The relationship between [Li / P]-[X / P] and [Al / P] preferably satisfies both of the following formulas (a17) and (b17).
[0179] 2.97≤[Li / P]-[X / P]≤3.06···(a17)
[0180] 0.05≤[Al / P]≤0.08···(b17)
[0181] When both the equations (a17) and (b17) are satisfied, the difference T2-T1 between the crystallization temperature T1 and the crystallization temperature T2 of the solid electrolyte becomes larger, thereby improving the productivity of the solid electrolyte.
[0182] The relationship between [Li / P]-[X / P] and [Al / P] also preferably satisfies all of the following formulae (b18), (c18) and (d18).
[0183] 0.01≤[Al / P]≤0.05···(b18)
[0184] [Li / P]-[X / P]≥-4.00×[Al / P]+3.01···(c18)
[0185] [Li / P]-[X / P]≥4.00×[Al / P]+2.77···(d18)
[0186] When all of the formulas (b18), (c18) and (d18) are satisfied, the crystallization temperature T1 is lowered, thereby improving the productivity of the solid electrolyte.
[0187] The relationship between [Li / P]-[X / P] and [Al / P] preferably satisfies both of the following formulas (a19) and (b19).
[0188] 2.97≤[Li / P]-[X / P]≤3.15···(a19)
[0189] 0.01≤[Al / P]≤0.08···(b19)
[0190] When both the formulas (a19) and (b19) are satisfied, the crystallization temperature T1 is lowered, thereby improving the productivity of the solid electrolyte.
[0191] [Li / P]-[X / P] is greater than 2.84 and less than 3.15, preferably greater than 2.85 and less than 3.10, more preferably greater than 2.89 and less than 3.07, further preferably greater than 2.90 and less than 3.05, further preferably 2.92 to 3.02, further preferably 2.94 to 3.00. By setting [Li / P]-[X / P] to the above range, the content of lithium element not bonded to the halogen element becomes appropriate, and the ion conductivity of the solid electrolyte is further improved.
[0192] [Li / P] is preferably 3.00 to 4.00, more preferably 3.20 to 3.90, further preferably 3.30 to 3.85, further preferably 3.40 to 3.80, further preferably 3.45 to 3.75.
[0193] [X / P] is preferably 0.10 to 1.00, more preferably 0.20 to 0.90, further preferably 0.30 to 0.80, and further preferably 0.40 to 0.70.
[0194] When both bromine and iodine are contained as halogen elements, the molar ratio of the bromine content to the phosphorus content [Br / P] is preferably 0.05 to 0.50, more preferably 0.10 to 0.45, further preferably 0.15 to 0.40, and further preferably 0.20 to 0.35.
[0195] When both bromine and iodine are contained as halogen elements, the molar ratio of the iodine content to the phosphorus content [I / P] is preferably 0.05 to 0.50, more preferably 0.10 to 0.45, further preferably 0.15 to 0.40, and further preferably 0.20 to 0.35.
[0196] [Al / P] is 0.01 to 0.10. The lower limit of [Al / P] may be 0.02, 0.03, 0.04 or 0.05. The upper limit of [Al / P] may be 0.08, 0.07, 0.06, 0.05, 0.04 or 0.03. [Al / P] may be above any of the lower limits and below any of the upper limits.
[0197] The molar ratio [S / P] of the sulfur content to the phosphorus content is preferably 3.50 to 4.50, more preferably 3.60 to 4.40, and even more preferably 3.70 to 4.30.
[0198] When the molar ratio of the content of lithium, halogen, bromine, iodine, aluminum or sulfur to the content of phosphorus, i.e. [Li / P], [X / P], [Br / P], [I / P], [Al / P] or [S / P], is within the above ranges, the ion conductivity is further improved due to the better crystal structure.
[0199] The solid electrolyte preferably further contains nitrogen. The molar ratio [N / P] of the nitrogen content to the phosphorus content can be 0.00 to 0.30, preferably 0.01 to 0.25, more preferably 0.02 to 0.20, and further preferably 0.03 to 0.15. When the solid electrolyte contains nitrogen, and the nitrogen content is within the above range, the ion conductivity is further improved. In particular, when the solid electrolyte further contains nitrogen, and when both the above formulas (a5) and (b5), both formulas (a6) and (b6), or both formulas (a7) and (b7) are satisfied, and further when both the above formulas (a8) and (b8), both formulas (a9) and (b9), or both formulas (a10) and (b10) are satisfied, the ion conductivity of the solid electrolyte is further improved.
[0200] The solid electrolyte may further contain zinc element. The molar ratio of the content of zinc element to the content of phosphorus element [Zn / P] is preferably 0.00 or more and less than 0.10, more preferably 0.001 to 0.05, and even more preferably 0.005 to 0.03.
[0201] The solid electrolyte may also include other elements (Y) except lithium, phosphorus, sulfur, halogen, aluminum, nitrogen and zinc. Other elements (Y) may be one or more. The molar ratio [Y / P] of the total content of the other elements (Y) relative to the content of phosphorus is preferably 0.04 or less, more preferably 0.03 or less, 0.02 or less, 0.01 or less or 0.00. In the case where the solid electrolyte does not contain other elements (Y) or the content of other elements (Y) is small, the essential elements can effectively play a role, so the ionic conductivity is further improved.
[0202] In the solid electrolyte, as the above-mentioned other element (Y), it is preferred that the boron element is not contained, or even if the boron element is contained, the molar basis content of the boron element is preferably less than the molar basis content of the aluminum element. That is, the molar ratio [B / Al] of the content of the boron element relative to the content of the aluminum element is preferably less than 1.00, and more preferably less than 0.50, less than 0.30, less than 0.20, less than 0.10 or less than 0.01. [B / Al] can be greater than 0.00 or 0.00. In this way, when the solid electrolyte does not contain the boron element or the content of the boron element is small, the ionic conductivity is further improved because the essential elements can effectively play their role and suppress the excessive generation of lithium element defects.
[0203] The solid electrolyte is preferably represented by the following formula (1).
[0204] Li a Al b Zn c PS d N e X f Y g ···(1)
[0205] In the above formula (1), X is a halogen element, and Y is an element other than lithium, aluminum, zinc, phosphorus, sulfur, nitrogen and halogen. a, b, c, d, e, f and g are numerical values for giving a stoichiometric ratio, a is a numerical value satisfying 3.00≤a≤4.00, b is a numerical value satisfying 0.01≤b≤0.10, c is a numerical value satisfying 0.00≤c<0.10, d is a numerical value satisfying 3.50≤d≤4.50, e is a numerical value satisfying 0.00≤e≤0.30, f is a numerical value satisfying 0.10≤f≤1.00, and g is a numerical value of 0.00≤g≤0.04.
[0206] When the solid electrolyte has a composition represented by the above formula (1), the ion conductivity is further improved. The suitable ranges of a, b, c, d, e, f and g in the above formula (1) are the same as the suitable ranges of the molar ratios of the contents of the above elements relative to the content of the phosphorus element. That is, the suitable range of a is the same as the suitable range of [Li / P], the suitable range of b is the same as the suitable range of [Al / P], the suitable range of c is the same as the suitable range of [Zn / P], the suitable range of d is the same as the suitable range of [S / P], the suitable range of e is the same as the suitable range of [N / P], the suitable range of f is the same as the suitable range of [X / P], and the suitable range of g is the same as the suitable range of [Y / P].
[0207] (Physical properties, uses, etc.)
[0208] The lower limit of the ionic conductivity of the solid electrolyte at 25°C is preferably 4.7 mS / cm, more preferably 4.8 mS / cm, further preferably 4.9 mS / cm, and further preferably 5.0 mS / cm. By making the ionic conductivity of the solid electrolyte at 25°C above the above lower limit, the charge and discharge performance of the storage element having the solid electrolyte can be improved. The upper limit of the above ionic conductivity is not particularly limited, for example, it can be 20 mS / cm, or it can be 10 mS / cm or 8 mS / cm.
[0209] The "ionic conductivity" of the solid electrolyte is determined by measuring the AC impedance according to the following method. In an argon atmosphere with a dew point below -50°C, 120 mg of sample powder is placed in a powder molding machine with an inner diameter of 10 mm, and then uniaxially pressed at 50 MPa or less using a hydraulic press. After the pressure is released, 120 mg of SUS316L powder is placed on the top of the sample as a current collector, and then uniaxially pressed at 50 MPa or less using a hydraulic press again. Next, 120 mg of SUS316L powder is placed under the sample as a current collector, and then uniaxially pressed at 360 MPa for 5 minutes to obtain particles for ionic conductivity measurement. The particles for ionic conductivity measurement are inserted into a HS battery cell manufactured by Hohsen Corporation, and AC impedance is measured at a specified temperature. The measurement conditions are set to an applied voltage amplitude of 20 mV, a frequency range of 1 MHz to 100 mHz, and a measurement temperature of 25°C.
[0210] The shape of the solid electrolyte is not particularly limited, and is generally granular, blocky, etc. The solid electrolyte can be used as a non-aqueous electrolyte for storage elements such as lithium ion secondary batteries, especially lithium ion storage elements. Among them, it can be particularly suitable for use as a non-aqueous electrolyte for all-solid-state batteries. It should be noted that the solid electrolyte can be used for any one of the positive electrode layer, the separator layer, the negative electrode layer, etc. of the storage element.
[0211] <Method for producing solid electrolyte>
[0212] The method for producing a solid electrolyte according to an embodiment of the present invention is not particularly limited, and includes, for example, the steps of preparing a composition containing lithium, phosphorus, sulfur, a halogen, and aluminum, and treating the composition.
[0213] (Preparation process)
[0214] The composition used as a raw material in the manufacturing method is usually a mixture of two or more compounds or simple substances (hereinafter, also referred to as compounds, etc.) containing at least one element of lithium, phosphorus, sulfur, halogen and aluminum. Any one of the compounds contained in the above-mentioned composition (mixture) may contain lithium, phosphorus, sulfur, halogen and aluminum. It is also possible to contain two or more elements of lithium, phosphorus, sulfur, halogen and aluminum in one compound. The above-mentioned composition may also be a composition containing a compound that does not contain any one of lithium, phosphorus, sulfur, halogen and aluminum.
[0215] Examples of compounds containing lithium include Li2S, Li2O, Li3N, Li2CO3, and metallic lithium. In addition, LiBr, LiI, Li 1.5 Al 0.5 N, etc. Among these, Li2S, LiBr, LiI and Li 1.5 Al 0.5 N. A compound containing a lithium element may be used alone or in combination of two or more.
[0216] Examples of compounds containing phosphorus include P2S3, P2S5, P2O5, P3N5, elemental phosphorus, etc. Among these, P2S3 and P2S5 are preferred, and P2S5 is more preferred. One compound containing phosphorus may be used alone, or two or more compounds may be used in combination.
[0217] Examples of compounds containing sulfur include Li2S, P2S3, P2S5, Al2S3, MgS, SiS2, elemental sulfur, etc. Among these, Li2S, P2S3, P2S5, and Al2S3 are preferred. One type of compound containing sulfur may be used alone, or two or more types may be mixed and used.
[0218] Examples of the halogen-containing compound include LiF, LiCl, LiBr, LiI, ZnBr, Zn 0.5 I, F2, Cl2, Br2, I2, etc. Among these, LiI, LiBr and Zn are preferred.0.5 I.
[0219] As the compound containing aluminum element, a compound containing aluminum element and nitrogen element is preferred, and Li α Al β n γ The compounds represented by (α, β and γ are numerical values given to the stoichiometric ratio). α Al β n γ The compound represented (hereinafter also referred to as a compound containing Li-Al-N) can be produced according to the following steps. First, prepare a lithium nitride (such as Li3N) and an aluminum nitride (such as AlN), and mix them in a mortar or the like. Next, make particles of the mixed raw material compounds. Next, by heat-treating the particles, a compound containing Li-Al-N is produced. It should be noted that the means for preparing a compound containing Li-Al-N is not limited to this, and it can also be produced according to other methods. For example, the raw materials of the compound containing Li-Al-N can be two or more compounds containing any one of lithium, aluminum and nitrogen. The compound containing Li-Al-N can be produced by mechanical grinding. As a compound containing Li-Al-N, a compound that is industrially produced and sold can be prepared.
[0220] As the Li—Al—N-containing compound, Li is preferably used from the viewpoint of easy availability and control of nitrogen emission to the outside of the system during the production process of the solid electrolyte. 1.5 Al 0.5 N.
[0221] Examples of the compound containing aluminum include, among others, aluminum oxides, aluminum sulfides, aluminum nitrides, and alloys of aluminum and lithium. Examples of aluminum sulfides include Al2S3. Examples of aluminum nitrides include AlN. One type of compound containing aluminum may be used alone, or two or more types may be mixed and used.
[0222] The composition preferably contains nitrogen. That is, the composition preferably contains a compound containing nitrogen. Examples of the compound containing nitrogen include the above-mentioned Li3N, P3N5, a compound containing Li—Al—N, and AlN.
[0223] For example, as an embodiment, the above composition may also include Li2S, P2S5, Li 1.5 Al 0.5 N, LiI, LiBr and Zn 0.5As another embodiment, the composition may also include Li2S, P2S5, Al2S3, LiI, LiBr and Zn 0.5 The composition of I.
[0224] In the above composition, the compounds are mixed so that the constituent elements satisfy both the above formulas (a1) and (b1) or both the above formulas (a2) and (b2). The appropriate content of each element in the above composition is the same as the appropriate content of each element in the sulfide solid electrolyte according to one embodiment of the present invention.
[0225] (Processing steps)
[0226] In the manufacturing method, the above composition is treated to obtain a solid electrolyte. As the above treatment, a method of obtaining an intermediate by mechanical grinding and heating the intermediate can be cited. It should be noted that the means for obtaining the intermediate is not limited to this, and methods other than mechanical grinding, such as a melt rapid cooling method, etc. can also be performed.
[0227] Mechanical grinding can be any of dry and wet, and wet is preferred in order to be able to mix the raw material compounds more evenly. As mechanical grinding, for example, grinding, roller milling, jet milling, etc. using a container-driven mill, a medium-stirred mill, a high-speed rotary pulverizer, etc. can be cited. As a container-driven mill, for example, a rotary mill, a vibrating mill, a planetary mill, etc. can be cited. As a medium-stirred mill, for example, a grinding mill, a bead mill, etc. can be cited. As grinding using a high-speed rotary pulverizer, for example, a hammer mill, a pin mill, etc. can be cited. Among these, a container-driven mill is preferred, and a planetary mill is particularly preferred.
[0228] The intermediate obtained by mechanical grinding or the like may have a crystalline structure, but is preferably a so-called sulfide glass. "Sulfide glass" refers to a sulfide solid electrolyte containing an amorphous structure. If the intermediate is sulfide glass, there are fewer crystalline phases with low stability such as Li2S, and a solid electrolyte with highly dispersed elements can be obtained.
[0229] The intermediate obtained by mechanical grinding or the like is heated (heat treated). Thus, a solid electrolyte in which at least a portion of the intermediate is crystallized, preferably at least a portion of the intermediate is crystallized into HICP or the like can be obtained. The heating (heat treatment) can be performed in a reduced pressure atmosphere or in an inert atmosphere.
[0230] As the lower limit of the above-mentioned heating temperature, based on the crystallization temperature T1 of the precipitation of the above-mentioned HICP, etc., it is preferably T1-20 [°C], more preferably T1 [°C], and further preferably T1+10 [°C]. On the other hand, as the upper limit of the above-mentioned heating temperature, based on the crystallization temperature T2 of the precipitation of the above-mentioned β-Li3PS4, etc., it is preferably T2-20 [°C], more preferably T2-30 [°C], and further preferably T2-40 [°C]. By making the above-mentioned heating temperature above the above-mentioned lower limit, the precipitation of HICP, etc. with high ion conductivity can be promoted. In addition, by making the above-mentioned heating temperature below the above-mentioned upper limit, the phase transformation into β-Li3PS4, etc. with low ion conductivity can be suppressed.
[0231] <Electrical storage element>
[0232] As one embodiment of the electric storage device of the present invention, an all-solid-state battery will be described below as a specific example. Figure 1 The storage element 10 shown is an all-solid-state battery, which is a secondary battery composed of a positive electrode layer 1 and a negative electrode layer 2 arranged via a separator 3. The positive electrode layer 1 has a positive electrode substrate 4 and a positive electrode active material layer 5, and the positive electrode substrate 4 is the outermost layer of the positive electrode layer 1. The negative electrode layer 2 has a negative electrode substrate 7 and a negative electrode active material layer 6, and the negative electrode substrate 7 is the outermost layer of the negative electrode layer 2. Figure 1 In the illustrated electric storage element 10 , a negative electrode active material layer 6 , a separator 3 , a positive electrode active material layer 5 , and a positive electrode substrate 4 are sequentially stacked on a negative electrode substrate 7 .
[0233] In the storage element 10, at least one of the positive electrode layer 1, the negative electrode layer 2, and the separator 3 contains the solid electrolyte according to one embodiment of the present invention. More specifically, at least one of the positive electrode active material layer 5, the negative electrode active material layer 6, and the separator 3 contains the solid electrolyte according to one embodiment of the present invention. Since the storage element 10 contains the solid electrolyte with high ion conductivity, the charge and discharge performance is good.
[0234] In the storage element 10, other solid electrolytes other than the solid electrolyte involved in one embodiment of the present invention may also be used in combination. As other solid electrolytes, sulfide solid electrolytes, oxide solid electrolytes, dry polymer electrolytes, gel polymer electrolytes, quasi-solid electrolytes, etc. other than the solid electrolyte involved in one embodiment of the present invention may be cited, preferably sulfide solid electrolytes. In addition, a layer in the storage element 10 may contain a plurality of different solid electrolytes, or each layer may contain a different solid electrolyte.
[0235] Examples of sulfide solid electrolytes other than the solid electrolyte according to one embodiment of the present invention include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-Li3N, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S 2n (where m and n are positive numbers, and Z is any one of Ge, Zn, and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In), Li 10 GeP2S 12 wait.
[0236] (Positive electrode layer)
[0237] The positive electrode layer 1 includes a positive electrode substrate 4 and a positive electrode active material layer 5 laminated on the surface of the positive electrode substrate 4. The positive electrode layer 1 may further include an intermediate layer between the positive electrode substrate 4 and the positive electrode active material layer 5.
[0238] The positive electrode substrate 4 has electrical conductivity. Whether it has "electrical conductivity" is determined by a volume resistivity 10 measured in accordance with JIS-H-0505 (1975). -2 Ω·cm is the threshold for judgment. As the material of the positive electrode substrate 4, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among them, from the viewpoint of potential resistance, electrical conductivity and cost, aluminum or aluminum alloys are preferred. As the positive electrode substrate 4, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate 4. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H4160 (2006) can be cited.
[0239] The average thickness of the positive electrode substrate 4 is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By making the average thickness of the positive electrode substrate 4 within the above range, the strength of the positive electrode substrate 4 can be improved, and the energy density per unit volume of the storage element 10 can be improved. The "average thickness" is the average value of the thickness measured at any five positions (the same applies to the average thickness below).
[0240] The intermediate layer is a layer disposed between the positive electrode substrate 4 and the positive electrode active material layer 5. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate 4 and the positive electrode active material layer 5. The structure of the intermediate layer is not particularly limited, and for example, contains a binder and a conductive agent.
[0241] The positive electrode active material layer 5 contains a positive electrode active material. The positive electrode active material layer 5 can be formed of a so-called positive electrode mixture containing a positive electrode active material. The positive electrode active material layer 5 can also contain a mixture or a composite containing a positive electrode active material and a solid electrolyte. The positive electrode active material layer 5 contains any component such as a conductive agent, a binder (adhesive), a thickener, and a filler as required. The positive electrode active material layer 5 may also not substantially contain one or more of these arbitrary components.
[0242] As the positive electrode active material, it can be appropriately selected from known positive electrode active materials. As the positive electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. As the positive electrode active material, for example, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel crystal structure, polyanion compounds, chalcogen compounds, sulfur, etc. can be cited. As lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, for example, Li[Li x Ni (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ CO (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x CO (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β CO (1-x-γ-β)]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ CO β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β) etc. As lithium transition metal composite oxides having a spinel crystal structure, Li x Mn2O4、Li x Ni γ Mn (2-γ) O4, etc. As polyanion compounds, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be cited. As chalcogenides, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be cited. The atoms or polyanions in these materials can be partially replaced by atoms or anionic substances composed of other elements. The surfaces of these materials can also be coated with other materials. In the positive electrode active material layer 5, one of these materials can be used alone, or two or more can be mixed and used.
[0243] The positive electrode active material is generally in the form of particles (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm to 20 μm. By making the average particle size of the positive electrode active material above the above lower limit, the manufacture or handling of the positive electrode active material is facilitated. By making the average particle size of the positive electrode active material below the above upper limit, the electron conductivity of the positive electrode active material layer 5 is improved. It should be noted that when a composite of the positive electrode active material and other materials is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. "Average particle size" refers to the particle size distribution measured by the laser diffraction / scattering method based on the diluted solution after the particles are diluted in a solvent in accordance with JIS-Z-8825 (2013), and the volume standard cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%.
[0244] In order to obtain a powder of a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, methods such as using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow type jet mill, or a sieve can be cited. During pulverization, wet pulverization coexisting with organic solvents such as water or hexane can also be used. As a classification method, a sieve, a wind classifier, etc. can be used, but dry or wet methods can be used as needed.
[0245] The content of the positive electrode active material in the positive electrode active material layer 5 is preferably 10 mass % to 95 mass %, with a lower limit of 30 mass %, and more preferably 50 mass %. When the content of the positive electrode active material is within the above range, the discharge capacity of the energy storage device 10 can be increased.
[0246] When the positive electrode active material layer 5 contains a solid electrolyte, the content of the solid electrolyte is preferably 5% to 90% by mass, more preferably 20% to 70% by mass, and the upper limit is sometimes more preferably 50% by mass. By making the content of the solid electrolyte within the above range, the discharge capacity of the storage element 10 can be increased. In the case where the positive electrode active material layer 5 uses a solid electrolyte according to an embodiment of the present invention, the content of the solid electrolyte according to an embodiment of the present invention in the positive electrode active material layer 5 relative to the total solid electrolyte is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and further preferably substantially 100% by mass.
[0247] The mixture of the positive electrode active material and the solid electrolyte is a mixture made by mixing the positive electrode active material and the solid electrolyte by mechanical grinding. For example, the mixture of the positive electrode active material and the solid electrolyte can be obtained by mixing a particulate positive electrode active material and a particulate solid electrolyte. As a composite of the positive electrode active material and the solid electrolyte, there can be cited a composite having a chemical or physical bond between the positive electrode active material and the solid electrolyte, a composite formed by mechanically compounding the positive electrode active material with the solid electrolyte, etc. The above-mentioned composite is a substance in which the positive electrode active material and the solid electrolyte exist in one particle, for example, a substance in which the positive electrode active material and the solid electrolyte form a cohesive state, a substance in which a film containing a solid electrolyte is formed on at least a portion of the surface of the positive electrode active material, etc.
[0248] The conductive agent is not particularly limited as long as it is a material with conductivity. Examples of such conductive agents include carbon materials, metals, conductive ceramics, etc. Examples of carbon materials include graphite, non-graphite carbon, graphene-based carbon, etc. Examples of non-graphite carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, etc. Examples of carbon black include furnace black, acetylene black, Ketjen black, etc. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, etc. Examples of the shape of the conductive agent include powder, fiber, etc. Examples of the conductive agent include one of these materials alone, or a mixture of two or more. In addition, these materials may be used in combination. For example, a material composited with carbon black and CNT may be used. From the viewpoint of electronic conductivity and coating properties, carbon black is preferred among these, and acetylene black is preferred.
[0249] The content of the conductive agent in the positive electrode active material layer 5 is preferably 1% to 10% by mass, and more preferably 3% to 9% by mass. When the content of the conductive agent is within the above range, the energy density of the electric storage device 10 can be increased.
[0250] As adhesives, for example, there can be mentioned thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0251] The content of the binder in the positive electrode active material layer 5 is preferably 1% by mass to 10% by mass, and more preferably 3% by mass to 9% by mass. When the content of the binder is within the above range, the positive electrode active material can be stably retained.
[0252] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be inactivated in advance by methylation or the like.
[0253] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other mineral resources or their artificial products.
[0254] The positive electrode active material layer 5 may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, etc. as components other than the positive electrode active material, solid electrolyte, conductive agent, adhesive, thickener, and filler; typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, etc.; and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W.
[0255] The average thickness of the positive electrode active material layer 5 is preferably 30 μm to 1000 μm, and more preferably 60 μm to 500 μm. By making the average thickness of the positive electrode active material layer 5 greater than or equal to the above lower limit, a storage element 10 having a high energy density can be obtained. By making the average thickness of the positive electrode active material layer 5 less than or equal to the above upper limit, the storage element 10 can be miniaturized.
[0256] (Negative electrode layer)
[0257] The negative electrode layer 2 includes a negative electrode substrate 7 and a negative electrode active material layer 6 disposed directly or via an intermediate layer on the negative electrode substrate 7. The structure of the intermediate layer is not particularly limited and can be selected from the structures exemplified for the positive electrode layer 1, for example.
[0258] The negative electrode substrate 7 has conductivity. As the material of the negative electrode substrate 7, metals such as copper, nickel, stainless steel, nickel-plated steel, aluminum, or their alloys, carbon materials, etc. can be used. Among them, copper or copper alloys are preferred. As the negative electrode substrate 7, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate 7, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.
[0259] The average thickness of the negative electrode substrate 7 is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate 7 within the above range, the strength of the negative electrode substrate 7 can be improved, and the energy density per unit volume of the storage element 10 can be improved.
[0260] The negative electrode active material layer 6 contains a negative electrode active material. The negative electrode active material layer 6 can be formed of a so-called negative electrode mixture containing a negative electrode active material. The negative electrode active material layer 6 can also contain a mixture or a composite containing a negative electrode active material and a solid electrolyte. The negative electrode active material layer 6 contains any components such as a conductive agent, a binder, a thickener, and a filler as needed. The types and appropriate contents of the arbitrary components in these negative electrode active material layers 6 are the same as those of the above-mentioned arbitrary components of the positive electrode active material layer 5. The negative electrode active material layer 6 may also be substantially free of one or more of these arbitrary components.
[0261] The negative electrode active material layer 6 may contain, as components other than the positive electrode active material, solid electrolyte, conductive agent, adhesive, thickener, and filler, typical non-metallic elements such as B, N, P, F, Cl, Br, and I; typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba; and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W.
[0262] The negative electrode active material can be appropriately selected from known negative electrode active materials. Negative electrode active materials for lithium ion secondary batteries generally use materials that can absorb and release lithium ions. Examples of negative electrode active materials include metallic lithium; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12, LiTiO2, TiNb2O7 and other titanium-containing oxides; polyphosphate compounds; silicon carbide; carbon materials such as graphite and non-graphite carbon (easy graphite carbon or difficult graphite carbon). Among these materials, graphite and non-graphite carbon are preferred. In the negative electrode active material layer 6, one of these materials can be used alone, or two or more can be mixed and used.
[0263] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before charge or discharge or in the discharged state. 002 ) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. From the perspective of obtaining a material with stable physical properties, artificial graphite is preferred.
[0264] “Non-graphite carbon” refers to the average lattice spacing (d ) of the (002) plane determined by X-ray diffraction before charge / discharge or in the discharged state. 002 ) is a carbon material having a diameter of 0.34 nm to 0.42 nm. Examples of non-graphite carbon include hard graphite carbon and easy graphite carbon. Examples of non-graphite carbon include materials derived from resins, petroleum asphalt or materials derived from petroleum asphalt, petroleum coke or materials derived from petroleum coke, materials derived from plants, and materials derived from alcohols.
[0265] Here, the "discharge state" refers to a discharge state in which lithium ions that can be absorbed and released from the carbonaceous material as the negative electrode active material are fully released during charge and discharge. For example, in a half-cell having a negative electrode containing a carbonaceous material as the negative electrode active material as the working electrode and metallic lithium as the counter electrode, the open circuit voltage is 0.7V or more.
[0266] "Difficult to graphitize carbon" refers to the above-mentioned 002 It is a carbon material with a diameter of 0.36nm to 0.42nm.
[0267] "Easily graphitizable carbon" refers to the above-mentioned 002 It is a carbon material with a diameter of 0.34nm to 0.36nm.
[0268] The negative electrode active material is generally a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm to 100 μm. When the negative electrode active material is a carbon material, a titanium oxide or a polyphosphate compound, its average particle size can also be 1 μm to 100 μm. When the negative electrode active material is Si, Sn, Si oxide or Sn oxide, etc., its average particle size can also be 1 nm to 1 μm. By setting the average particle size of the negative electrode active material to above the above lower limit, it is easy to manufacture or handle the negative electrode active material. By making the average particle size of the negative electrode active material below the above upper limit, the electronic conductivity of the negative electrode active material layer 6 is improved. In order to obtain a powder of a specified particle size, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected from the methods exemplified in the positive electrode layer 1, for example. When the negative electrode active material is a metal such as metallic lithium, the negative electrode active material layer 6 can also be in the form of a foil.
[0269] The content of the negative electrode active material in the negative electrode active material layer 6 is preferably 10 mass % to 95 mass %, with a lower limit of 30 mass %, and more preferably 50 mass %. When the content of the negative electrode active material is within the above range, the discharge capacity of the energy storage device 10 can be increased.
[0270] When the negative electrode active material layer 6 contains a solid electrolyte, the content of the solid electrolyte is preferably 5% to 90% by mass, more preferably 20% to 70% by mass, and the upper limit is sometimes further preferably 50% by mass. By making the content of the solid electrolyte within the above range, the discharge capacity of the storage element 10 can be increased. When the negative electrode active material layer 6 uses a solid electrolyte according to an embodiment of the present invention, the content of the solid electrolyte according to an embodiment of the present invention in the negative electrode active material layer 6 relative to the total solid electrolyte is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and further preferably substantially 100% by mass.
[0271] The mixture or composite of the negative electrode active material and the solid electrolyte etc. may be a mixture or composite of the positive electrode active material and the solid electrolyte etc. described above, in which the positive electrode active material is replaced by the negative electrode active material.
[0272] The average thickness of the negative electrode active material layer 6 is preferably 30 μm to 1000 μm, and more preferably 60 μm to 500 μm. By making the average thickness of the negative electrode active material layer 6 equal to or greater than the above lower limit, a storage element 10 having a high energy density can be obtained. By making the average thickness of the negative electrode active material layer 6 equal to or less than the above upper limit, the storage element 10 can be miniaturized.
[0273] (Isolation layer)
[0274] The separator 3 contains a solid electrolyte. The content of the solid electrolyte in the separator 3 is preferably 70% by mass or more, more preferably 90% by mass or more, further preferably 99% by mass or more, and further preferably substantially 100% by mass. In addition, when the separator 3 uses the solid electrolyte according to one embodiment of the present invention, the content of the solid electrolyte according to one embodiment of the present invention in the separator 3 relative to the total solid electrolyte is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and further preferably substantially 100% by mass.
[0275] Separation layer 3 may further contain any component such as phosphate compounds such as Li3PO4, oxides, halides, binders, thickeners, fillers, etc. The binders, thickeners, fillers, etc. may be selected from the materials exemplified for positive electrode active material layer 5.
[0276] The average thickness of the separator 3 is preferably 1 μm to 50 μm, and more preferably 3 μm to 20 μm. By making the average thickness of the separator 3 equal to or greater than the above lower limit, the positive electrode layer 1 and the negative electrode layer 2 can be insulated with high reliability. By making the average thickness of the separator 3 equal to or less than the above upper limit, the energy density of the storage element 10 can be increased.
[0277] The storage element of this embodiment can be installed as a storage unit (battery module) composed of a plurality of storage elements in an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc., a car power source, a personal computer, a communication terminal, etc. In this case, the technology of the present invention can be applied to at least one storage element contained in the storage unit.
[0278] Figure 2 , an example of an electric storage device 30 is shown in which an electric storage unit 20 formed by aggregating two or more electric storage elements 10 that are electrically connected is further assembled. The electric storage device 30 may also include a bus bar (not shown) that electrically connects the two or more electric storage elements 10, a bus bar (not shown) that electrically connects the two or more electric storage units 20, etc. The electric storage unit 20 or the electric storage device 30 may also include a state monitoring device (not shown) that monitors the state of the one or more electric storage elements 10.
[0279] <Method for manufacturing energy storage device>
[0280] In a method for manufacturing a storage element according to an embodiment of the present invention, a solid electrolyte according to an embodiment of the present invention is used as part or all of the solid electrolyte in the production of at least one of the positive electrode layer, the separator layer, and the negative electrode layer, and other methods generally known in the art are used. Specifically, the manufacturing method comprises, for example, (1) a step of preparing a positive electrode mixture, (2) a step of preparing a material for a separator layer, (3) a step of preparing a negative electrode mixture, and (4) a step of stacking a positive electrode layer, a separator layer, and a negative electrode layer. Each step is described in detail below.
[0281] (1) Positive electrode mixture preparation process
[0282] In this process, a positive electrode mixture for forming a positive electrode layer (positive electrode active material layer) is usually prepared. There is no particular limitation on the method for preparing the positive electrode mixture, and it can be appropriately selected according to the purpose. For example, mechanical grinding treatment of the material of the positive electrode mixture, compression molding of the positive electrode active material, sputtering of a target material using the positive electrode active material, etc. can be cited. When the positive electrode mixture contains a mixture or a composite comprising a positive electrode active material and a solid electrolyte, this process may include, for example, using a mechanical grinding method to mix the positive electrode active material with the solid electrolyte and prepare a mixture or a composite of the positive electrode active material and the solid electrolyte.
[0283] (2) Preparation process of materials for isolation layer
[0284] In this process, a material for an isolation layer is usually prepared to form an isolation layer. When the storage element is an all-solid-state battery, the isolation layer material can be a solid electrolyte. The solid electrolyte used as the isolation layer material can be prepared according to a conventionally known method. For example, a mechanical grinding method can be used to obtain a specified material. The isolation layer material can be prepared by a melt rapid cooling method in which a specified material is heated to a temperature above the melting temperature, the material is melt-mixed at a specified ratio, and rapidly cooled. Other methods for synthesizing isolation layer materials include, for example, a solid phase method of reduced pressure sealing and firing, a liquid phase method such as dissolution separation, a gas phase method (PLD), and firing in an argon atmosphere after mechanical grinding.
[0285] (3) Negative electrode mixture preparation process
[0286] In this process, a negative electrode mixture for forming a negative electrode layer (negative electrode active material layer) is usually prepared. The specific preparation method of the negative electrode mixture is the same as that of the positive electrode mixture. When the negative electrode mixture contains a mixture or a complex containing a negative electrode active material and a solid electrolyte, this process may include a step of mixing the negative electrode active material with the solid electrolyte and preparing a mixture or a complex of the negative electrode active material and the solid electrolyte, for example, using a mechanical grinding method.
[0287] (4) Lamination process
[0288] In this process, for example, a positive electrode layer having a positive electrode substrate and a positive electrode active material layer, a separator layer, and a negative electrode layer having a negative electrode substrate and a negative electrode active material layer are stacked. In this process, the positive electrode layer, the separator layer, and the negative electrode layer can be formed in sequence, or vice versa, and the order of formation of each layer is not particularly limited. The above-mentioned positive electrode layer is formed, for example, by press-molding the positive electrode substrate and the positive electrode mixture, the above-mentioned separator layer is formed by press-molding the separator layer material, and the above-mentioned negative electrode layer is formed by press-molding the negative electrode substrate and the negative electrode mixture. It is also possible to press-mold the positive electrode substrate, the positive electrode mixture, the separator layer material, the negative electrode mixture, and the negative electrode substrate at one time, thereby stacking the positive electrode layer, the separator layer, and the negative electrode layer. It is also possible to pre-mold the positive electrode layer and the negative electrode layer separately, and then press-mold them with the separator layer to stack them.
[0289] <Other embodiments>
[0290] It should be noted that the solid electrolyte and the storage element of the present invention are not limited to the above-mentioned embodiments, and various changes can be made within the scope of the gist of the present invention. For example, the structure of other embodiments can be added to the structure of one embodiment, and a part of the structure of one embodiment can be replaced with the structure of other embodiments or known technology. Furthermore, a part of the structure of one embodiment can be deleted. In addition, known technology can be added to the structure of one embodiment.
[0291] For example, the storage element of the present invention may also have other layers in addition to the positive electrode layer, the separator layer and the negative electrode layer. The present invention may also be applicable to storage elements having bipolar electrodes. In addition, the storage element of the present invention may also contain a liquid. As such a storage element, for example, a storage element in which the gaps between the positive electrode active material layer 5, the separator layer 3 and the negative electrode active material layer 6 of the above-mentioned storage element 10 are filled with a non-aqueous electrolyte containing an ionic liquid or the like can be cited. The storage element of the present invention may be a capacitor or the like in addition to a secondary battery, i.e., a storage element.
[0292] <Example>
[0293] Hereinafter, the present invention will be further specifically described by way of examples, but the present invention is not limited to the following examples.
[0294] [Example 1]
[0295] The solid electrolyte of Example 1 satisfying the composition ratio described in Table 1 was synthesized by the following treatment.
[0296] First, Li3N and AlN were weighed to a molar ratio of 1.2:1, mixed in a mortar, and pelletized. Then, Li3N and AlN were heat treated at 750°C for 1 hour to prepare Li 1.5Al 0.5 N. These steps are carried out in an argon atmosphere with a dew point below -50°C. 1.5 Al 0.5 N, and the main phase was confirmed to be Li by X-ray diffraction measurement. 1.5 Al 0.5 N.
[0297] Li2S (99.98%, manufactured by Aldrich), P2S5 (99%, manufactured by Aldrich), Li 1.5 Al 0.5 N, LiBr (99.999%, Aldrich), LiI (99.999%, Aldrich), and Zn 0.5 I (99.999%, manufactured by Aldrich) was added to give a molar ratio of 53.97:19.14:4.08:11.13:11.00:0.66, and then mixed in a mortar to prepare a composition containing lithium, phosphorus, sulfur, bromine, iodine, aluminum, nitrogen and zinc as constituent elements.
[0298] The composition was placed in an 80 mL zirconia sealed pot containing 160 g of zirconia balls with a diameter of 4 mm, and subjected to mechanical milling treatment at a revolution speed of 510 rpm for 45 hours using a planetary ball mill (FRITSCH, model number: Premium line PL-7) to obtain an intermediate.
[0299] The intermediate was heated at 210°C for 2 hours (heat treatment) to obtain the solid electrolyte of Example 1. The heat treatment temperature HT[°C] was set within the range of T1-20°C or higher and T2-20°C or lower, based on the above-mentioned crystallization temperature T1[°C] and the above-mentioned crystallization temperature T2[°C]. It should be noted that the crystallization temperature T1[°C] and the crystallization temperature T2[°C] were obtained by taking out a part of the intermediate after the mechanical grinding treatment and measuring DSC by the above-mentioned method.
[0300] [Examples 2 to 13, Comparative Examples 1 to 9]
[0301] The compounds used as raw materials and their amounts (molar ratios) were adjusted so that the composition ratios of the solid electrolytes were as shown in Tables 1 and 2. The heat treatment temperature was as shown in Tables 1 and 2. Except for this, the same procedure as in Example 1 was followed to obtain solid electrolytes of Examples 2 to 13 and Comparative Examples 1 to 9.
[0302] It should be noted that in Example 2 and Comparative Examples 1, 7, and 9, Li 1.5 Al 0.5 N, or with Li1.5 Al 0.5 N together with Li 1.5 B 0.5 N. Li 1.5 B 0.5 N was prepared as follows. Li3N and BN were weighed to a molar ratio of 1.2:1, mixed in a mortar and pelletized. Then, Li3N was heat treated at 800°C for 10 minutes to obtain Li 1.5 B 0.5 N. These processes are carried out in an argon atmosphere with a dew point below -50°C.
[0303] In addition, in Examples 3 and 4, Al2S3 was used instead of Li 1.5 Al 0.5 N. In Comparative Examples 1 to 3, Li 1.5 Al 0.5 N, in Comparative Examples 7 to 9, no halides (LiBr, LiI and Zn 0.5 I).
[0304] The heat treatment temperature HT[°C] of Examples 2 to 9, Examples 11 to 13, and Comparative Examples 1 to 6 was set in the same manner as in Example 1. The heat treatment temperature HT[°C] of Example 10 was also set within the range of T1-20°C or higher and T2-20°C or lower, and the specific heat treatment temperature was 190°C. The heat treatment temperature HT[°C] of Comparative Examples 7 to 9 was set to a temperature that was higher than the crystallization temperature within the range of room temperature to 400°C and was less than 100°C higher than the crystallization temperature.
[0305] Regarding the constituent elements of each solid electrolyte of Examples 1 to 13 and Comparative Examples 1 to 6, the molar ratio of the lithium element content to the phosphorus element content [Li / P], the molar ratio of the sulfur element content to the phosphorus element content [S / P], the molar ratio of the aluminum element content to the phosphorus element content [Al / P], the molar ratio of the boron element content to the phosphorus element content [B / P], the molar ratio of the nitrogen element content to the phosphorus element content [N / P], the molar ratio of the halogen element (bromine element and iodine element) content to the phosphorus element content [X / P], the molar ratio of the zinc element content to the phosphorus element content [Zn / P], and the difference between [Li / P] and [X / P] [Li / P] - [X / P] are shown in Table 1. In addition, regarding the constituent elements of each solid electrolyte of Comparative Examples 7 to 9, the molar ratio of the content of lithium element to the content of phosphorus element [Li / P], the molar ratio of the content of sulfur element to the content of phosphorus element [S / P], the molar ratio of the content of aluminum element to the content of phosphorus element [Al / P], the molar ratio of the content of boron element to the content of phosphorus element [B / P], the molar ratio of the content of nitrogen element to the content of phosphorus element [N / P], the molar ratio of the content of halogen element (bromine element and iodine element) to the content of phosphorus element [X / P], and the molar ratio of the content of zinc element to the content of phosphorus element [Zn / P] are shown in Table 2. It should be noted that in each solid electrolyte of Examples 1 to 13 and Comparative Examples 1 to 9, it can be considered that no elements other than phosphorus element, lithium element, sulfur element, aluminum element, boron element, nitrogen element, bromine element, iodine element and zinc element are substantially contained. That is, for example, the composition formula of the solid electrolyte of Example 1 is Li 3.56 Al 0.05 Zn 0.01 PS 3.91 N 0.11 Br 0.29 I 0.30 .
[0306] In addition, for each solid electrolyte of Examples 1 to 13 and Comparative Examples 1 to 6, the crystallization temperature T1 [°C], the crystallization temperature T2 [°C], the difference in crystallization temperature T2-T1 [°C], the heat treatment temperature HT [°C], and the crystal structure confirmed by the X-ray diffraction pattern measured by powder X-ray diffraction using the above method are shown in Table 1. For each solid electrolyte of Comparative Examples 7 to 9, the heat treatment temperature HT [°C] is shown in Table 2.
[0307] [Reference Example 1]
[0308] Weighing Li2S and Li 1.5 Al 0.5N to make the molar ratio of 87.5:12.5, and mix in a mortar. 0.40 g of the obtained mixture was put into an 80 mL zirconia sealed jar containing 50 g of zirconia balls with a diameter of 4 mm. These steps were carried out in an argon atmosphere with a dew point below -50°C. A planetary ball mill (made by FRITSCH, model Premium line PL-7) was used to treat at a revolution speed of 400 rpm for 1000 minutes to obtain the solid electrolyte of Reference Example 1.
[0309] [Reference Example 2]
[0310] Li 1.5 Al 0.5 N is changed to Li 1.5 B 0.5 N. Except for this, the same procedure as in Reference Example 1 was carried out to obtain a solid electrolyte of Reference Example 2.
[0311] Regarding the constituent elements of each solid electrolyte of Reference Examples 1 and 2, the molar ratio of the content of lithium element to the content of sulfur element [Li / S], the molar ratio of the content of aluminum element to the content of sulfur element [Al / S], the molar ratio of the content of boron element to the content of sulfur element [B / S], and the molar ratio of the content of nitrogen element to the content of sulfur element [N / S] are shown in Table 3. It should be noted that each solid electrolyte of Reference Examples 1 and 2 is considered to contain substantially no elements other than sulfur element, lithium element, aluminum element, boron element, and nitrogen element.
[0312] [evaluate]
[0313] The AC impedance was measured by the above method using "VMP-300" manufactured by Bio-Logic, and the ionic conductivity (σ 25 ). The measurement results are shown in Tables 1 to 3. In addition, the scatter plots showing the relationship between the values of [Li / P]-[X / P] and [Al / P] and the ion conductivity in Examples 1 to 13 and Comparative Examples 1 to 6 are shown in Figure 3 . Figure 3 The numerical value of each point in the table is the ion conductivity [mS / cm] of the solid electrolyte corresponding to each point. Figure 3 .
[0314]
[0315] [Table 2]
[0316]
[0317] [Table 3]
[0318]
[0319] As shown in Tables 1 and 2, the solid electrolytes of Comparative Examples 1 to 3 that do not contain aluminum, Comparative Example 4 that has a high aluminum content ([Al / P]), Comparative Example 5 that has a low aluminum content ([Al / P]), Comparative Example 6 that has a low content of lithium not combined with a halogen element ([Li / P] - [X / P]), and Comparative Examples 7 to 9 that do not contain a halogen element have low ion conductivity. In contrast, the solid electrolytes of Examples 1 to 13 that contain lithium, phosphorus, sulfur, halogen, and aluminum and satisfy both the above-mentioned formulas (a1) and (b1) or both the formulas (a2) and (b2) have high ion conductivity. In addition, Figure 3 As shown, it can be seen that when [Li / P]-[X / P] and [Al / P] are within the prescribed ranges, the ion conductivity is high.
[0320] It should be noted that, as shown in Table 3, the solid electrolyte of Reference Example 1 containing aluminum in the solid electrolyte containing lithium and sulfur has a higher ion conductivity than the solid electrolyte of Reference Example 2 containing boron in the solid electrolyte containing lithium and sulfur. On the other hand, as shown in Table 1, for example, the solid electrolyte of Example 1 containing aluminum in the solid electrolyte containing lithium, phosphorus and sulfur has a higher ion conductivity than the solid electrolyte of Comparative Example 1 containing boron in the solid electrolyte containing lithium, phosphorus and sulfur. It can be confirmed that the effect of improving ion conductivity due to the inclusion of aluminum is a unique effect produced when the solid electrolyte containing aluminum is contained relative to the solid electrolyte containing lithium, phosphorus and sulfur.
[0321] The solid electrolyte according to the present invention can be suitably used as a solid electrolyte for power storage devices such as all-solid-state batteries.
[0322] Explanation of symbols
[0323] 1 Positive electrode layer
[0324] 2 Negative electrode layer
[0325] 3 Isolation layer
[0326] 4. Cathode substrate
[0327] 5 Positive electrode active material layer
[0328] 6 Negative electrode active material layer
[0329] 7 Negative electrode substrate
[0330] 10 Energy storage element (all-solid-state battery)
[0331] 20 Storage unit
[0332] 30 Power storage device
Claims
1. A solid electrolyte comprising lithium, phosphorus, sulfur, halogen and aluminum. Has a crystalline structure, Satisfying both the following formulas (a1) and (b1) or satisfying both the following formulas (a2) and (b2), 2.89<[Li / P]-[X / P]≤3.15···(a1) 0.01≤[Al / P]≤0.10···(b1) 2.84<[Li / P]-[X / P]≤2.89···(a2) 0.02≤[Al / P]≤0.10···(b2) In the formulas (a1), (b1), (a2) and (b2), [Li / P] is the molar ratio of the lithium element content to the phosphorus element content, [X / P] is the molar ratio of the halogen element content to the phosphorus element content, and [Al / P] is the molar ratio of the aluminum element content to the phosphorus element content.
2. The solid electrolyte according to claim 1, wherein Does not contain boron, or The aluminum alloy further contains a boron element, and the molar content of the boron element is less than the molar content of the aluminum element.
3. The solid electrolyte according to claim 1 or 2, wherein It further contains nitrogen.
4. The solid electrolyte according to claim 3, wherein Satisfying both the following equations (a3) and (b3), 2.92≤[Li / P]-[X / P]≤3.07···(a3) 0.01≤[Al / P]≤0.07···(b3).
5. The solid electrolyte according to claim 1 or 2, which is represented by the following formula (1): Li a Al b Zn c PS d N e X f Y g ···(1) In the formula (1), X is a halogen element, Y is an element other than lithium, aluminum, zinc, phosphorus, sulfur, nitrogen and halogen; a, b, c, d, e, f and g are numerical values assigned to the stoichiometric ratio, a is a numerical value satisfying 3.00≤a≤4.00, b is a numerical value satisfying 0.01≤b≤0.10, c is a numerical value satisfying 0.00≤c<0.10, d is a numerical value satisfying 3.50≤d≤4.50, e is a numerical value satisfying 0.00≤e≤0.30, f is a numerical value satisfying 0.10≤f≤1.00, and g is a numerical value satisfying 0.00≤g≤0.
04.
6. The solid electrolyte according to claim 1, which satisfies both of the following formulas (a4) and (b4), 2.94≤[Li / P]-[X / P]≤3.05···(a4) 0.01≤[Al / P]≤0.06···(b4).
7. The solid electrolyte according to claim 1, which satisfies both of the following formulas (a5) and (b5), or satisfies both of the following formulas (a6) and (b6), or satisfies both of the following formulas (a7) and (b7), 3.05<[Li / P]-[X / P]≤3.15···(a5) 0.03≤[Al / P]≤0.08···(b5) 2.91<[Li / P]-[X / P]≤3.05···(a6) 0.01≤[Al / P]≤0.10···(b6) 2.84<[Li / P]-[X / P]≤2.91···(a7) 0.03≤[Al / P]≤0.08···(b7).
8. The solid electrolyte according to claim 1, which satisfies both of the following formulas (a8) and (b8), or satisfies both of the following formulas (a9) and (b9), or satisfies both of the following formulas (a10) and (b10), 3.00<[Li / P]-[X / P]≤3.15···(a8) 0.04≤[Al / P]≤0.07···(b8) 2.93<[Li / P]-[X / P]≤3.00···(a9) 0.01≤[Al / P]≤0.09···(b9) 2.84<[Li / P]-[X / P]≤2.93···(a10) 0.04≤[Al / P]≤0.07···(b10).
9. The solid electrolyte according to claim 1, which satisfies both of the following formulas (a11) and (b11): 2.87<[Li / P]-[X / P]≤3.06···(a11) 0.03≤[Al / P]≤0.08···(b11).
10. The solid electrolyte according to claim 1, which satisfies all of the following formulas (b12), (c12) and (d12), 0.01≤[Al / P]≤0.03···(b12) [Li / P]-[X / P]≤5.00×[Al / P]+2.91···(c12) [Li / P]-[X / P]≥-3.50×[Al / P]+2.98···(d12).
11. The solid electrolyte according to claim 1, which satisfies all of the following formulas (b13), (c13) and (d13), 0.03≤[Al / P]≤0.08···(b13) [Li / P]-[X / P]≤3.50×[Al / P]+2.96···(c13) [Li / P]-[X / P]≤-2.33×[Al / P]+3.25···(d13).
12. The solid electrolyte according to claim 1, which satisfies both of the following formulas (a14) and (b14), 2.97≤[Li / P]-[X / P]≤3.06···(a14) 0.01≤[Al / P]≤0.05···(b14).
13. The solid electrolyte according to claim 1, which satisfies all of the following formulas (a15), (b15) and (c15), 2.97≤[Li / P]-[X / P]≤3.06···(a15) 0.01≤[Al / P]≤0.03···(b15) [Li / P]-[X / P]≤5.00×[Al / P]+2.91···(c15).
14. The solid electrolyte according to claim 1, which satisfies both of the following formulas (a16) and (b16), 2.97≤[Li / P]-[X / P]≤3.06···(a16) 0.03≤[Al / P]≤0.05···(b16).
15. The solid electrolyte according to claim 1, wherein Both bromine and iodine are contained as halogen elements, and the molar ratio [Br / P] of the content of bromine to the content of phosphorus is 0.05 to 0.
50.
16. The solid electrolyte according to claim 1, wherein Both bromine and iodine are contained as halogen elements, and the molar ratio [I / P] of the content of the iodine element to the content of the phosphorus element is 0.05 to 0.
50.
17. The solid electrolyte according to claim 1, wherein The molar ratio [S / P] of the sulfur content to the phosphorus content is 3.50 to 4.
50.
18. The solid electrolyte according to claim 3, wherein The molar ratio [N / P] of the nitrogen content to the phosphorus content is 0.01 to 0.
25.
19. The solid electrolyte according to claim 1, wherein It further contains zinc, The molar ratio of the content of zinc element to the content of phosphorus element [Zn / P] is 0.001 to 0.
05.
20. The solid electrolyte according to claim 1, which satisfies both of the following formulas (a17) and (b17), 2.97≤[Li / P]-[X / P]≤3.06···(a17) 0.05≤[Al / P]≤0.08···(b17).
21. The solid electrolyte according to claim 1, which satisfies all of the following formulas (b18), (c18) and (d18), 0.01≤[Al / P]≤0.05···(b18) [Li / P]-[X / P]≥-4.00×[Al / P]+3.01···(c18) [Li / P]-[X / P]≥4.00×[Al / P]+2.77···(d18).
22. The solid electrolyte according to claim 1, which satisfies both of the following formulas (a19) and (b19), 2.97≤[Li / P]-[X / P]≤3.15···(a19) 0.01≤[Al / P]≤0.08···(b19). 23 . An electric storage element comprising the solid electrolyte according to claim 1 , 2 or 6 to 17 or claim 19 to 22 .
Citation Information
Patent Citations
Lithium ion conductive sulfide based crystallized glass and its manufacturing method
JP2005228570A